RESPON POPULASI Eucalyptus occidentalis TERHADAP SELEKSI KONDISI GARAM TINGGI PADA UJI TERKONTROL DAN UJI LAPANGAN - Rina Laksmi Hendrati (Jurnal Pemuliaan Tanaman Hutan, 2010)
Global changes together with rising number of human population, industrial development, and exploitation of natural vegetation, are the main factors causing high salinity in many regions of the world. Trees tolerant to grow in saline regions are crucially needed and can be used as an effective means to control or even decrease salinity. Eucalyptus occidentalis, a Western Australia native tree spesies that is highly tolerant to salt has a wide range of natural habitats from waterlogged, highly saline to arid regions. Selections of provenances and families from throughout its natural distribution are needed to identify the most tolerant genotypes within this species. Comparative performances of E. occidentalis under salt and/or waterlogged conditions were investigated under controller condition and in field trial. An initial screening of 25 provenances was conducted for salt tolerance ranging from 0 mM to 300 mM under control, waterlogged, dry salt and salt treatments. Nine provenances selected from the first screening were exposed to similar treatments up to 550 mM of salt concentration. The same seed collections of 23 provenances were germinated at the same time and planted in field trial in Roberts, South Western Australia. Salt concentration of 300 mM did not affect E. occidentalis growth, and therefore it is not an appropriate level for selection. Under 550 mM of salt concentration, plants were depressed and differences between provenaces are much more noticeable. There were different responses of E. occidentalis populations on selection under high salinity between controlled condition and in field trial.